Metabolism leaves its mark on the powerhouse: recent progress in post-translational modifications of lysine in mitochondria - Papanicolaou, Kyriakos N.; O'Rourke, Brian; Foster, D. Brian (Frontiers in Physiology, 2014)
Lysine modifications have been studied extensively in the nucleus, where they play pivotal roles in gene regulation and constitute one of the pillars of epigenetics. In the cytoplasm, they are critical to proteostasis. However, in the last decade we have also witnessed the emergence of mitochondria as prime locus for post-translational modification of lysine thanks, in large measure, to evolving proteomic techniques. Here, were we review recent work on evolving set of post-translational modifications that arise from the direct reaction of lysine residues with energized metabolic thioester-coenzyme A intermediates, including acetylation, succinylation, malonylation and glutarylation. We highlight the evolutionary conservation, kinetics, stoichiometry and cross-talk between members of this emerging family of PTMs. We examine the impact on target protein function and regulation by mitochondrial sirtuins. Finally, we spotlight work in the heart and cardiac mitochondria, and consider the roles acetylation and other newly-found modifications may play in heart disease.